A new pan-chelydrid turtle, Tavachelydra stevensoni gen. et sp. nov., from the lower Paleocene (early Danian, Puercan) Corral Bluffs Study Area in the Denver Basin, Colorado - Tyler R. Lyson; Holger Petermann; Salvador Bastien; Natalie Toth; Evan Tamez-Galvan; Sadie M. Sherman; Walter G. Joyce (Swiss Journal of Palaeontology)
Abstract Isolated pan-chelydrid turtle shell fragments are common in Late Cretaceous and early Paleocene sediments across western North America, but more complete and associated specimens are rare, obfuscating our understanding of the group’s early evolution. Here we describe a new genus and species, Tavachelydra stevensoni, of stem-chelydrid turtle from the early Paleocene of the Denver Formation (Danian, Puercan I and II) of Colorado based on complete shells, associated pelvic material, and referred cranial material. Our phylogenetic analysis places T. stevensoni as the immediate sister to crown chelydrids based on, among others, a purely ligamentous attachment of the plastron and carapace. The costiform process of the nuchal, an important character complex in chelydroid turtles, shows variation in either ending in peripheral II or III. The T. stevensoni material was mostly found in laminated fine-grained deposits, suggesting this taxon inhabited ponded-water environments. The referred cranial material shows broad triturating surfaces indicating a durophagous diet, further underscoring durophagy as an important feeding strategy during the early Paleocene.